Prevalence of dry eye symptoms and associated risk factors among students at Al-Mustaqbal University, Iraq - Hassan A. Aljaberi; Saeed Rahmani; Zainab A. Elzahra; Samir H. Mohammed (PLoS ONE, 2025)
This study aimed to estimate the prevalence, severity, and risk factors of dry eye symptoms (DES) among Iraqi university students and to examine associations with digital device use in an arid, dust-prone setting. A cross-sectional survey was conducted at Al-Mustaqbal University (Iraq) between February and May 2025 using paper-based questionnaires that captured demographics, device-use patterns, symptom burden, and self-management behaviors. Symptom severity was assessed with the Ocular Surface Disease Index (OSDI), and DES prevalence was estimated using the Women’s Health Study (WHS) questionnaire. Binary logistic regression was applied to calculate adjusted odds ratios (aORs) with 95% confidence intervals (CIs). Among 1,487 invited students, 1,154 completed the survey (response rate 77.6%); participants were aged 19–24 years, and 63.6% were female. The WHS-defined prevalence of symptomatic DES was 62.0%. Blurred vision, burning, and ocular redness were the most frequent symptoms. A dose–response relationship was observed between daily screen time and OSDI severity, with the highest burden among students reporting more than 7 hours per day (trend p < 0.001). In adjusted models, female participants had higher odds (aOR 2.34; 95% CI 1.56–3.56; p < 0.001), screen time >7 h/day (aOR 2.25; 95% CI 1.55–3.31; p < 0.001), fourth academic year (aOR 1.75; 95% CI 1.18–2.60; p = 0.01), and use of glasses/contact lenses (aOR 1.45; 95% CI 1.10–1.90; p = 0.01) were significant predictors. Laptops were most often associated with ocular redness, smartphones with burning and pain, and tablets with blurred vision. In conclusion, DES symptoms were highly prevalent and strongly associated with prolonged daily screen exposure. Female sex, advanced academic standing, and corrective lens use further increased risk. Findings support campus-level prevention focused on digital hygiene, ergonomic optimization, and periodic ocular screening, considering environmental stressors typical of arid, dust-prone settings.